Extracellular matrix change in patients with various forms of atrial fibrillation - A. V. Goryachiy; A. I. Gozhenko; E. M. Levchenko; V. V. Goriachyi; M. A. Kuznetsova; M. I. Arapu (Journal of Education, Health and Sport, 2017)
Purpose: We studied the change in serum collagen markers in patients with various forms of atrial fibrillation (AF) Methods: Collagen type C-terminal propeptide (CTPK-I), C-terminal telopeptide of type I collagen (CTTK-I), matrix metalloproteinase I, and tissue inhibitors of matrix metalloproteinase I were used as markers for collagen synthesis. The study group comprised - 70 people, control - 20. Results: The level of CTCP-I and CTTP-I in patients with AF was significantly higher in comparison with the control group (91 +27 ng / ml, 67 + 11 ng / ml, p